A comparative clinical study among intermaxillary fixation screw, Erich arch bar and Ivy eyelet in mandibular fracture - Yadav, Deepak; Chaurasia, Nitesh; Mishra, Ravish; Kandel, Laxmi; Ali, Shahid (Journal of Gandaki Medical College-Nepal, 2024)
Introduction: Management of mandibular fractures requires intermaxillary fixation (IMF) as an adjunct to open reduction and internal fixation (ORIF). IMF is fixing mandible to maxilla with the help of a metallic framework around teeth or dentoalveolar segment to secure correct inter-arch relationship before plating. The methods for IMF are Erich Arch bars and Ivy Eyelet and IMF screw. Thus, the aim of this study was to compare the outcomes of IMF screws, Erich arch bar and Ivy Eyelet in achieving intraoperative IMF. Methods: The study included 45 patients with mandibular fracture who underwent ORIF and required IMF as part of treatment, under general anesthesia. Patients were divided equally into three groups. Group A: patients who were treated using Erich arch bars, Group B: patients who were treated using Ivy Eyelets and Group C: patients who were treated using IMF screws. The outcomes were compared among three groups to draw an inference on surgical time, gloves perforation and post-operative occlusion. Results: The study showed mandibular fractures among 16 to 52 years of age with mean age of 26.62 ± 8.497 years, more common in 21 to 30 years of age groups. The median time were 65 minute, 28 minute and 35 minute for Erich arch bar, Ivy eyelet and IMF screw respectively (p<0.05). Gloves perforation was present in all cases of Group A, nine cases of Group B and only four cases of group C (p<0.05). There was no significant difference in post-operative occlusion among three groups (p>0.05). Conclusions: IMF screw was more effective than Erich arch bar and Ivy eyelet in terms of surgical time and gloves perforation.